Phosphorus‐containing polyhedral oligomeric silsesquioxane/polyimides hybrid materials with low dielectric constant and low coefficients of thermal expansion. Issue 39 (2nd July 2015) - Li, Xuesong; Hao, Jinmeng; Jiang, Qiyang; Mu, Jianxin; Jiang, Zhenhua
ABSTRACT Novel phosphorus‐containing polyhedral oligomeric silsesquioxane (POSS)/polyimides (PI) hybrid materials with low dielectric constant and low linear coefficients of thermal expansion (CTE) were prepared and characterized. The POSS/PI hybrid materials were synthesized with octa(aminopropyl)silsesquioxane (OAPS) and a series of phosphorus‐containing polyamide acids(PAA). The PAAs were synthesized with bis(4‐aminophenoxy) phenyl phosphine oxide (BAPPO), 4, 4'‐diaminodiphenyl ether (ODA) and 3, 3', 4, 4'‐biphenyl tetracarboxylic diandhydride (BPDA). The structures and properties of the hybrid materials were characterized. And the effect of the phosphorus‐containing structure on the POSS/PI hybrid materials was discussed. The dielectric constants and CTE of the hybrid materials were remarkably lower than that of the unmodified POSS/PI films. The lowest values of dielectric constant and CTE could achieve as low as 2.64 (1 MHz) and 27.45 ppm/K. Besides, the hybrid materials also had excellent thermal properties. The highest 5% weight loss temperature of the hybrid materials was as high as 580°C under air. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42611.